Konsep Geosciene Center Kali Ngalang - Arinta Destri Larasati; Primantoro Nur Vitrianto; Isdarmanto Isdarmanto (Ideas Publishing, 2023)
Tourism development at the Ngalang River Geosite has not been maximized. The purpose of this study is to find the new concept of tourism development in the region. The method used is deductive research which is qualitative in nature carried out in a descriptive which is exploratory in nature. The result of the research is the concept of geosciene center which refers to geotourism in Kali Ngalang. This concept emphasizes zoning aspects which are important for science and education.